The Role of Internet of Medical Things (IoMT) and Block Chain Technology for the Prevention of COVID-19 Pandemic Effect: Hafiz Burhan Ul Haq - Hafiz Burhan Ul Haq, Hafiz Burhan Ul Haq; Akifa Abbas, Akifa Abbas (International Journal for Electronic Crime Investigation, 2021)
Now a days, COVID-19 spreads everywhere and has severely affected across the globe. As COVID-19 spread in a fast manner, it creates an alarming situation all over the world. The health sector has faced more problems as compared to other sectors due to thousands of people reported per day, so the demand for oxygen pumps, masks, and sanitizers has also increased. In this situation both public and private sectors plays an important role to make the country COVID-19 free. Both private and public sectors worked hard and developed a number of IoT and Blockchain technologies, adopting different methodologies to deal with COVID-19. This paper presents the number of IoT and Blockchain technologies like (IoT Buttons, Robots, Reporting and testing ways, telemedicine) are used in COVID-19. Furthermore, it is also elaborated that how these techniques are useful with the help of case studies